Human rights in focus from Paulo Freire's thought: interpersonal dialogues - Amaral, Manoel Francisco do (Universidade Estadual de Campinas, 2022)
This text is a critical review. It is intended to reveal how the authors present the concept of human rights based on Paulo Freire's thought. It is a work written by several authors who seek the relationship between the liberating pedagogy and the multiple movements in favor of the oppressed layers. The relevance of reading the work in its entirety is already considered, for all those who intend to get closer to Paulo Freire's critical theory, as a tool in the struggle for an emancipatory and humanizing education.